Double‐C loop platform in combination with hydrophobic and hydrophilic acrylic intraocular lens materials. Issue 7 (July 2015) - Bozukova, Dimitriya; Werner, Liliana; Mamalis, Nick; Gobin, Laure; Pagnoulle, Christophe; Floyd, Anne; Liu, Erica; Stallings, Shannon; Morris, Caleb
Abstract : Purpose : To analyze the behavior of a new double‐C‐loop quadripod symmetrical intraocular lens (IOL) platform combined with a hydrophilic lens material and a new hydrophobic glistening‐free acrylic lens material, Ankoris and Podeye, respectively, in silico (computer simulation), in vitro (laboratory investigation), and in vivo (rabbit model). Setting : John A. Moran Eye Center, University of Utah, Salt Lake City, Utah, USA, and Physiol S.A., Liege, Belgium. Design : Experimental study. Methods : An in silico simulation investigation was performed using finite elements software, an in vitro investigation according to the International Organization for Standardization (ISO11979‐3:2012), and an in vivo implantation in a rabbit model with 4 weeks of follow‐up. Postmortem data were collected by Miyake‐Apple gross examination and histopathologic analyses. Biocompatibility and IOL centration were tested. Results : Both IOLs demonstrated statistically insignificant variations in posterior and anterior capsule opacification and Soemmerring ring formation. They were well biotolerated with no signs of toxicity, inflammation, or neovascularization. Axial and centration stability were noted in vitro and in vivo as a result of significant contact between surrounding tissues and haptics and the posterior portion of the optic. Conclusion : The results suggest suitability of the double‐C loop IOL platform for the manufacturing of premium (ie, multifocal, toric, and multifocal toric) IOLs. Financial Disclosure : Drs. Bozukova, Gobin, and Pagnoulle are employees of Physiol S.A., Liege, Belgium. Dr. Pagnoulle has a proprietary interest in the tested intraocular lenses. No other author has a financial or proprietary interest in any material or method mentioned.